Outcomes on the Utilization of Lipodermoid Skin for Anterior Lamella Reconstruction in Severe Lipodermoids With Eyelid Coloboma: A Case Series. Issue 1 (13th July 2022) - Islam, Meriam; Morrison, Danny; Hamada, Samer; Katowitz, James; Malhotra, Raman
Abstract : Two young children with upper lid colobomas and associated lipodermoids underwent eyelid reconstruction using lipodermoid skin as an autograft with good cosmesis. We describe their presentation, surgical management, and clinical progress following reconstruction, demonstrating the suitability of this skin as an adequate graft avoiding the need for further skin graft harvesting in such cases. Abstract : To describe a case series of 2 patients in which lipodermoid skin served as a suitable skin graft for anterior lamella reconstruction.